AI, Wage Dynamics, and Work-Life Balance in the E-Commerce Industry: A Literature Review - Rifki Arohman; Abd. Rasyid Syamsuri; M. Renaldy Saputra; Rofi Gemaladi Hibatullah (Penerbit Merdeka Kreasi, 2025)
This study aims to explore the intersections of artificial intelligence, wage dynamics, and work-life balance in the context of the e-commerce industry, with particular attention to how digital transformation reshapes human resource management practices. Using a literature review method, the research systematically analyzed peer-reviewed journal articles, academic books, and reputable reports published in the last five years, focusing on themes related to algorithmic management, compensation structures, and employee well-being. The findings highlight that AI contributes significantly to wage optimization, predictive workforce planning, and performance evaluation, thereby improving organizational efficiency and responsiveness. However, the results also reveal critical challenges such as algorithmic bias, wage inequity, heightened employee monitoring, and the potential erosion of boundaries between work and personal life. These insights underscore the dual role of AI as both an enabler of productivity and a source of ethical dilemmas within e-commerce workplaces. The study concludes that successful integration of AI requires balanced strategies that combine technological innovation with human-centered values, ensuring fairness, inclusivity, and sustainable work practices in the digital economy.